DEVONIAN STAGE BOUNDARIES IN NOVAYA ZEMLYA - Cherkesova S.V.; Sobolev N.N.; Spassky Ya.N. (My University, 2001)
The Devonian stratigraphical succession of Novaya Zemlya has been discussed. In the area all standard boundaries have been recognised or traced using lithological (sedimentological) features and palaeontological data. The latter include conodonts, tentaculitids, brachiopods and rugose corals.
Keywords: Devonian; Novaya Zemlya; Paleozoic::Devonian; Палеозой::Девонская